2011
DOI: 10.1016/j.joep.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Are nurses more altruistic than real estate brokers?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
0
28
1
Order By: Relevance
“…With experimental (Jacobsen et al, 2011) andanecdotal (Miers et al, 2007;Shaw and Degazon, 2008) evidence suggesting that nurses are likely to be more altruistic than the general population, does it make studying the role of social preferences in career decisions in that population less relevant or interesting? We believe not.…”
Section: Discussionmentioning
confidence: 99%
“…With experimental (Jacobsen et al, 2011) andanecdotal (Miers et al, 2007;Shaw and Degazon, 2008) evidence suggesting that nurses are likely to be more altruistic than the general population, does it make studying the role of social preferences in career decisions in that population less relevant or interesting? We believe not.…”
Section: Discussionmentioning
confidence: 99%
“…It may, for instance, be a reasonable assumption that life professions attract individuals who are more altruistic and more medically fragile. One experimental study shows that generosity was higher among student nurses than real-estate broker students; however, this was probably more out of moral obligation rather than pure altruism (Jacobsen, Eika, Helland, Lind, & Nyborg, 2011). It is also possible that those who choose high-risk professional educational programs are more vulnerable individuals at the outset of the education in other respects.…”
Section: Discussionmentioning
confidence: 99%
“…Altruism is not only an expression of internal motivation but also a means by which to unify and ensure survival of a social group. Other researchers have also suggested that nurses are not necessarily more altruistic than other occupational groups but rather that they comply to a larger degree with a strong helping norm that characterizes the profession (Jacobsen et al 2011). This reasoning implies that altruistic values are a big part of the socialization of nurses and that they are not necessarily just associated with an internal motivation to enter nursing.…”
Section: Why Is This Research Needed?mentioning
confidence: 99%